Blinded comparison of mirror and endoscopic oral examination in the horse: Sensitivity, specificity and observer agreement. (26th July 2022) - Chiero, Naomi E.; Reiswig, Jeffrey D.; Griffin, Cleet E.; Panigrahi, Kathryn J.; Gardner, Alison K.
Summary: Background: Dental disease is commonly encountered in equine veterinary practice. Due to the horse's deep oral cavity, direct visual examination alone is not adequate for a complete oral evaluation. Typically, a long‐handled dental mirror is used as a visual aid. Oral endoscopy is another option to improve visual examination of the mouth. Although recent literature suggests endoscopy is superior to mirror examination, these modalities have not been compared in a blinded study. Objective: The objective of the study was to compare the sensitivity and specificity of identifying dental pathologies between oral mirror and rigid endoscopic examination, as well as evaluating the inter‐ and intra‐observer variability of each modality. Study design: Prospective randomised trial. Methods: Twenty‐one horses underwent oral examination using a mirror and an endoscope with video recording of both techniques. An additional six horses received both premortem and post‐mortem examinations. Two blinded observers evaluated the video recordings and identified the presence of dental pathology to determine inter‐observer and intraobserver agreement. Live examinations were compared with the six post‐mortem examinations to determine sensitivity and specificity. Results: Endoscopy sensitivity was far superior to mirror for all pathologies (83% vs. 39%), while specificity was high for both (71% vs. 87%, respectively) when compared to the gold‐standard post‐mortem examination. Inter‐observer agreement for the presence of pathology using endoscopy was substantial and higher than mirror examination. Intra‐observer agreement was moderate to substantial. Main limitations: The study was limited by the small number of horses and post‐mortem examinations, although sample size was increased by assessing the pathology of each tooth. Conclusions: Moderate to substantial agreement was found using both endoscopy and mirror examination. Sensitivity was improved with endoscopy. Oral endoscopy may be beneficial for use in monitoring dental disease over time, as many minor pathologies do not require immediate intervention. Endoscopic and mirror videos may also prove valuable in veterinary education.